2011
DOI: 10.3109/09286586.2011.560745
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Low Vision Service Provision

Abstract: This global survey provides the first consolidated baseline of low vision service provision. Where data are available, coverage of services is generally poor. Low vision health professional numbers are low. Services in over half of the world's countries are funded by NGOs, raising issues of sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 24 publications
0
88
1
2
Order By: Relevance
“…A global questionnaire survey showed that approximately half of the African and Western Pacific regions countries did not provide LVS, and very few countries had more than 10 vision rehabilitation professionals per 10 million of population. 42 Our reconsideration and classification of the need for specific eye care services are prompted by the difficulties in identifying and classifying individuals who need eye care. This framework is not definitive, and is intended as an operational approach for epidemiologic survey only.…”
Section: Discussionmentioning
confidence: 99%
“…A global questionnaire survey showed that approximately half of the African and Western Pacific regions countries did not provide LVS, and very few countries had more than 10 vision rehabilitation professionals per 10 million of population. 42 Our reconsideration and classification of the need for specific eye care services are prompted by the difficulties in identifying and classifying individuals who need eye care. This framework is not definitive, and is intended as an operational approach for epidemiologic survey only.…”
Section: Discussionmentioning
confidence: 99%
“…Low vision care, initially a hospital-based service, focused on dispensing optical and non-optical devices, eventually evolved into a multidisciplinary holistic rehabilitative approach 60 . However, these services are still inadequate in many areas 61 . It is estimated that only 5-10% of the people needing low vision services access it with huge variation between regions and countries 61 .…”
Section: Emerging Challengesmentioning
confidence: 99%
“…However, these services are still inadequate in many areas 61 . It is estimated that only 5-10% of the people needing low vision services access it with huge variation between regions and countries 61 . With the recent technological advances, better access to appropriate low-vision care can now be made available to neglected populations.…”
Section: Emerging Challengesmentioning
confidence: 99%
“…However, of the estimated 70 million of the 124 million people with low vision who require services, 1 approximately 5-10% were estimated to have access to care. 2,3 The demands for low vision services will continue to grow due to the emerging global trends in ageing populations and changes in the epidemiology of vision impairment. 4,5 Consequently, to address the current and future needs of low vision services, a global mapping survey of services was conducted.…”
mentioning
confidence: 99%